SRATEGI PENGEMBANGAN USAHA JASA PENGINAPAN DENGAN PENDEKATAN BUSINESS MODEL CANVAS PADA DESTINASI WISATA BAHARI DI KABUPATEN KONAWE SELATAN - Sarita, Buyung (Fakultas Pertanian Universitas Halu Oleo, 2023)
One of the business models that is often used today is the Business Model Canvas. The Business Model Canvas (BMC) is to describe, visualize, assess and change old business models into simpler business models. The Business Model Canvas (BMC) is described with nine main blocks, namely Customer Segment, Value Proposition, Channel, Customer Relationship, Revenue Stream, Key Resources. Main), Key Activities (Key Activities), Key Partnership (Main Partnership), and Cost Structure (Cost Structure). Business actors in running their business are not just about making a profit but must also pay attention to the interests of consumers. The aim of the research is to determine the implementation of the business model canvas, the impact and obstacles of implementing the Bussinis Model Canvas on the design of the business model for developing accommodation services businesses in marine tourism destinations in South Konawe Regency. This type of research is a multisite study. In this research, researchers will visit the business location to observe, research and take part in ongoing activities, of course while maintaining a certain code of ethics (politeness and maintaining the good name of the Institute). To collect research data, the observation method, questionnaire method, and documentary method were used. Data analysis in this research uses the Miles and Huberman model data analysis technique, including data reduction, data display and conclusion drawing verification which are carried out simultaneously. The results of the research show that the implementation of Canvas Model Busines as a business strategy for Lodging Business Actors in South Konawe Regency Based on the results of research, studies, observations and field studies related to the Implementation of Canvas Model Busines as a business strategy for Lodging Business Actors in South Konawe Regency, especially Exell Lodging in Torobulu Village and Suban Amolengu Lodging without realizing it have been implemented in the respective blocks of the Business Model Canvas.